1988
DOI: 10.1021/bi00409a018
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease T1 is stabilized by cation and anion binding

Abstract: The stability of the folded conformation of ribonuclease T1 is increased by 0.8, 1.8, and 3.3 kcal/mol in the presence of 0.1 M NaCl, MgCl2, and Na2HPO4, respectively. This remarkable increase in the conformational stability results primarily from the preferential binding to the native protein of one Mg2+ or two Na+ ions at cation-binding sites and by the binding of one HPO4(2-) ion at an anion-binding site. Only modest binding constants, 6.2 (Na+), 155 (Mg2+), and 282 M-1 (HPO4(2-)), are required to account f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 52 publications
11
74
0
Order By: Relevance
“…In view of our results on the effect of neutral salts on the stability of ubiquitin, an alternative interpretation involving not only cation but anion binding as well can be suggested. Such an interpretation agrees with an earlier study by Pace and Grimsley (1988), which showed that both anion and cation binding sites are available on the RNase T1 molecule. The stabilizing effect of anions on the acid denatured states of proteins have been studied extensively by Hagihara et al, 1993).…”
Section: Effect Of Guanidinium Chloridesupporting
confidence: 93%
“…In view of our results on the effect of neutral salts on the stability of ubiquitin, an alternative interpretation involving not only cation but anion binding as well can be suggested. Such an interpretation agrees with an earlier study by Pace and Grimsley (1988), which showed that both anion and cation binding sites are available on the RNase T1 molecule. The stabilizing effect of anions on the acid denatured states of proteins have been studied extensively by Hagihara et al, 1993).…”
Section: Effect Of Guanidinium Chloridesupporting
confidence: 93%
“…In CM-RNase Tt, the formation of an additional salt bridge between CM-Glu-58 and Arg-77, hence between the two domains, is thought to stabilize the whole molecule. This explanation is in line with the fact that the conformation of RNase T~ is extremely stabilized by salts [4][5][6]8,10]. In addition, a local conformational change induced by the carboxymethylation may also contribute somewhat to the stabilization.…”
Section: Discussionsupporting
confidence: 68%
“…It is a single-chain globular protein of 104 amino acid residues and is unfolded reversibly by heating or addition of denaturants. Therefore, a number of studies on the stability and unfolding/refolding have been made by using differential scanning calorimetry and spectroscopic methods including circular dichroism and fluorescence measurements [4][5][6][7][8][9][10][11]. The thermodynamic analysis indicated that the unfolding equilibrium of RNase T~ is described by a two-state model [4,5,8].…”
Section: Rnase T (Ec 31273) Is a Guanyloribonuclease Secreted Bymentioning
confidence: 99%
“…On the assumption that the unfolding equilibrium of the protein in the presence of ligand follows a two-state mechanism represented by N ⅐ L i D ϩ ⌬n ⅐ L, where ⌬n represents the difference in the number of metal ions (L) bound to the protein in the native (N) and denatured (D) states, the ⌬n value was calculated by the equation: (Record et al, 1978;Pace & Grimsley, 1988), where ⌬G m is the free energy change for unfolding at the T m of the protein in the absence of the metal ion and a L is the activity of the metal ion (Lide, 1994). Since the relationship between ⌬⌬G, a L , and the dissociation constant Schellman (1975), the K d values were calculated from curve fitting of the ⌬⌬G versus a L data on the basis of a least square analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it would be informative to analyze the conformational stability of this protein and its active site mutants in the presence and absence of the metal cofactor at an alkaline pH at which the enzyme is functional. If these proteins were stabilized in the presence of the metal cofactors, it would be possible to determine the number of metal ions bound to the protein and the dissociation constant by the method that was used to analyze the binding of anions or cations to RNase T 1 (Pace and Grimsley, 1988). Since the role of each active site residue in the catalytic function of the enzyme is not fully understood, such studies would provide important information.…”
mentioning
confidence: 99%